2005
DOI: 10.1152/ajplung.00130.2005
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory innate immune proteins differentially modulate the neutrophil respiratory burst response to influenza A virus

Abstract: Oxidants and neutrophils contribute to lung injury during influenza A virus (IAV) infection. Surfactant protein (SP)-D plays a pivotal role in restricting IAV replication and inflammation in the first several days after infection. Despite its potent anti-inflammatory effects in vivo, preincubation of IAV with SP-D in vitro strongly increases neutrophil respiratory burst responses to the virus. Several factors are shown to modify this apparent proinflammatory effect of SP-D. Although multimeric forms of SP-D sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
51
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 43 publications
(58 reference statements)
0
51
0
1
Order By: Relevance
“…9). The sialic acid residues on gp340 mediate binding of some bacteria and viruses (18,43,44), and specific sialic acid adhesins, Hsa and GspB, have been identified in S. gordonii (45). Also, the AgI/II adhesins of viridans (oral) streptococci mediate binding to gp340 (17,18,46,47).…”
Section: Discussionmentioning
confidence: 99%
“…9). The sialic acid residues on gp340 mediate binding of some bacteria and viruses (18,43,44), and specific sialic acid adhesins, Hsa and GspB, have been identified in S. gordonii (45). Also, the AgI/II adhesins of viridans (oral) streptococci mediate binding to gp340 (17,18,46,47).…”
Section: Discussionmentioning
confidence: 99%
“…IAV triggers H 2 O 2 response by neutrophils and these are increased by preincubation of IAV with wild-type SP-Ds (3,19). SP-Dcdm retained the ability to increase neutrophil H 2 O 2 , but the NCRD did not (Fig.…”
Section: Neutrophil Respiratory Burst Responsesmentioning
confidence: 93%
“…Although similar receptors are present on neutrophils, it is not yet clear whether these mechanisms can be generally extrapolated to other phagocytic cells or microbial ligands. However, we have shown that binding of free SP-D to neutrophils down-regulates respiratory burst responses elicited by subsequent addition of IAV and that preformed SP-D-IAV complexes strongly up-regulate these responses (19).…”
mentioning
confidence: 87%
“…SP-D directly inhibits the infectivity of IAV and also modulates the interaction of IAV with neutrophils. SP-D promotes the uptake of IAV by neutrophils, and can either increase or reduce respiratory burst responses of neutrophils upon exposure to IAV, depending on whether SP-D is first incubated with IAV or neutrophils (26). SP-D also protects neutrophils against IAV-induced neutrophil dysfunction (20,21).…”
mentioning
confidence: 99%